Effect of Ajwa date pits powder (Phoenix dactylifera L.) on body composition, lipid profile and blood pressure in patients with hyperlipidemia: A randomized clinical trial - Parkha Nasrullah; Bismillah Sehar; Mahpara Safdar; Sadia Fatima; Falak Zeb; Jahan Shah; Atif Khan; Bilal Ahmed; Ali Alsubaie; Muhammad Zaman (Mashhad University of Medical Sciences, 2023)
Objective: To evaluate the effect of Ajwa dates pit powder (ADP) on lipid profile, body composition and blood pressure in patients with hyperlipidemia.Materials and Methods: This randomized controlled clinical study was carried out on 40 patients with total cholesterol >200 mg/dl, triglycerides >150 mg/dl and BMI >25, of either sex, aged 30-50 years, who were recruited through written consent. The patients were divided into two groups (n=20 each): the ADP and the control group (CG). All patients received the doctor's prescribed class A statin (Rosuvastatin/ Atorvastatin) 10 mg/day, while 2.7 g ADP was given on daily basis before breakfast with lukewarm water for 40 days and the control group received the same amount of wheat flour. Body composition, blood pressure and lipid profile were determined at baseline, and after 20 and 40 days. Data were analyzed by using SPSS and GraphPad Prism.Results: ADP significantly reduced body weight (p<0.001), BMI (p<0.001), fat mass, body fat percentage, visceral fat area and waist circumference compared to the control group. Similarly, ADP significantly (p=0.000) decreased the serum level of total cholesterol and low-density lipoprotein. Conclusion: ADP may have the potential to improve dyslipidemia and obesity.